TERAPI SHALAT TAHAJUD DALAM PENY TERAPI SHALAT TAHAJUD DALAM PENYEMBUHAN BERBAGAI PENYAKIT - Pebby Juliyan Saputra; M. Amin Sihabuddin; Neni Noviza (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2023)
This research is about Midnight Prayer Therapy in Healing Various Diseases (Study of Book Analysis of Midnight Prayer Therapy by Prof. Dr.Moh. Sholeh). With the aim of research to find out the therapy of midnight prayer in healing various physical-spiritual diseases and to find out what diseases can be cured through midnight therapy, to find out the stages of research on midnight prayer therapy. Researchers used a qualitative approach to the type of library research or literature. The data source in this study is an analysis as complete and accurate as possible regarding the concept of anxiety obtained from a book by Prof. Dr. Moh. Sholeh. The results of the study are that first, the midnight prayer will fulfill the two strategies above because the essence of the wisdom that can be obtained from prayer itself is to live realistically, always be optimistic in readiness to face various life problems faced so that people remain constructive. In an optimistic attitude, people will be awake and remain in a state of homeostasis. Homeostasis occurs due to feedback mechanisms that limit overreactions and maintain normal conditions. Second, mention medically and scientifically diseases that can be cured through the therapy of midnight prayers such as stress disorders, somatoform and artificial disorders, dissociative disorders, gender identity disorders and sexual disorders, anxiety, affective (mood) disorders, schizophrenia and other psychotic disorders, as well as personality disorders. Third, stage 1) immunologic immune system anatomy therapy, 2) psychoneurionology of midnight prayers and 3) therapy for the process of reducing cortisol for practitioners of midnight prayers